Zooplankton Diversity and Abundance in Shrimp Pond Ecosystem in the Presence of Sargassum plagyophyllum and Gracilaria verrucosa - Izzati, Munifatul (JURNAL SAINS DAN MATEMATIKA, 2011)
We studied zooplankton community structure in defferent ecosystem type where different species of aquatic plants are presented. The different in zooplankton community structure can be attributed to different aquatic plant species. We used two different species of aquatic plants, Sargassum plagyophyllum and Gracilaria verrucosa in shrimp pond ecosystem. Every aquatic plant species were replicated three times, and three enclosures without aquatic plant were used as controls. The different in morphological complexity of aquatic plant may affect zooplankton community structure. Our results indicated that the presence of aquatic plant differ in affecting zooplankton community structure. In general, pond with aquatic plant indicate more abundant and diverse of zooplankton. In the presence of Sargassum zooplankton was more abundant compared to the presence of Gracilaria. Whereas with Gracilaria, zooplankton biodiversity index were higher than with Sargassum. Â Keywords: zooplankton, sargassum plagyophyllum, Gracilaria verrucosa.